A programme to facilitate mentoring of community service nurses in rural province, South Africa. (2022) - Khunou, S.H.; Rakhudu, M.A.
Abstract: Background: The gap exists regarding a structured formal programme to facilitate mentoring of newly qualified nurses performing community service. Despite the pronouncement of the need to mentor the Community Service nurses (CSNs), there is paucity regarding mentoring the programme. This article, present the development of a programme to facilitate mentoring of CSNs in rural province of South Africa. Methods: The study was conducted in two phases, namely empirical and programme development. The empirical phase employed convergent parallel mixed method approach to describe the CSNs' and nurse managers' perceptions regarding mentoring of CSNs. Data collection during the empirical phase was achieved through self-administered mentoring questionnaires by 174 nurse and 224 CSNs. Simultaneously, semi- structured interviews were used on 28 CSNs and 27 nurse managers. The programme development phase followed data obtained from the empirical phase, literature review and application of Kellogg's Logic Model (KLM). Results: The mentoring programme was developed pronouncing a sequential KLM components required for mentoring the CSNs in this rural province. The components entailed the problem to be addressed, mentoring needs; mentoring resources; activities; expected outcomes and assumptions. Conclusion: The KLM components described in this study, clearly demonstrate the sequence of events that need to be followed facilitate the mentoring of CSNs. The programme amalgamated empirical evidence pertaining to the problems associated with inadequate mentoring, mentoring needs of both CSNs and managers, required mentoring resources, outputs and the expected outcomes. It is recommended that this programme should be applied to enhance the mentoring of the CSNs.